Respuesta :

Answer:

x = 3 ± [tex]\sqrt{24}[/tex]

or

x = 3 + [tex]\sqrt{24}[/tex], x = 3 - [tex]\sqrt{24}[/tex]

Step-by-step explanation:

given f(x) = 2(x - 3)^2 - 8, find when f(x) = 40

So, we plug in 40 for f(x) in the 1st equation and solve for x.  (Aim to got x on its own)

40 = 2 (x - 3)^2 - 8

+ 8          + 8

-----------------------------

48 = 2 (x - 3)^2

/2            /2

-----------------------------

24 = (x - 3)^2

square root both sides

--------------------

[tex]\sqrt{24}[/tex] = x - 3

x = 3 ± [tex]\sqrt{24}[/tex]